Reducing surgical site infections: mechanisms, risks and prevention - Vagholkar, Ketan; Bhambri, Chhavi; Paradkar, Isha; Naidu, Padmapriya; Dudala, Bindu; Karnatki, Barclay (International Surgery Journal, 2026)
Surgical site infections (SSIs) remain a leading cause of healthcare-associated infection with significant morbidity, mortality and cost. It is a surgeon’s nightmare. SSI risk is multifactorial, involving patient, procedure, perioperative management, microbial and institutional factors. Objectives were to synthesize current evidence on determinants of SSI, mechanisms linking risk factors to infection and evidence-based prevention strategies. Narrative synthesis of guidelines, randomized trials, systematic reviews and key observational studies. Patient comorbidities (diabetes, obesity, immunosuppression), colonization (S. aureus), nutritional status, smoking and age increase SSI risk. Procedure-related factors include contamination class, operative time, tissue handling, implants and emergency surgery. Perioperative management which includes timing and weight-based dosing of prophylactic antibiotics, antiseptic skin preparation (alcohol-based chlorhexidine superior in many settings), maintenance of normothermia, perioperative glycaemic control, hair clipping (not shaving) and sterile technique significantly affect SSI rates. Environmental and institutional factors (OR ventilation, sterilization practices, surveillance programs) and pathogen factors (biofilm formation, antimicrobial resistance) also drive SSI risk. Bundled, multimodal prevention programs such as targeted interventions (e.g., S. aureus decolonization for carriers) are effective in high-risk populations in reducing SSI rates. Reduction in SSI rates requires identification and optimization of modifiable patient and process risk factors, adherence to evidence-based perioperative practices and systems-level surveillance and stewardship.